2021
DOI: 10.1007/s11191-021-00286-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Life Philosophy and Major Field of Study on Brazilian Students’ Knowledge of Biological Evolution

Abstract: Evolutionary theory (ET) is the unifying theory of Life Sciences, but it is largely misunderstood and the target of dispute in many countries, mainly because of conflicts with religious beliefs. Brazil is a country with a culture that is deeply rooted belief in God. In this paper, we report a study in Brazil where we applied a 12-question questionnaire to understand the relationship among the major field of study and the self-declared religious and philosophical context on the knowledge of evolutionary theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…In our case, Italian Catholics had a higher acceptance as well as a higher level of understanding of evolution than Brazilian ones. Independent recent research obtained similar results, showing that Catholic and Evangelical Brazilian university students had low levels of knowledge about evolution [ 74 ].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In our case, Italian Catholics had a higher acceptance as well as a higher level of understanding of evolution than Brazilian ones. Independent recent research obtained similar results, showing that Catholic and Evangelical Brazilian university students had low levels of knowledge about evolution [ 74 ].…”
Section: Discussionmentioning
confidence: 65%
“…For instance, the level of acceptance of evolution has improved considerably within members of some conservative Christian denominations whose teachings are informed by cultural barriers to evolution [ 35 ]. Unfortunately, change can also be noticed in the opposite direction, with conservative anti-evolution groups and religious denominations showing a growing influence around the world, Brazil included [ 39 41 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent bibliometric mapping analysis of trends in science education research revealed that the examination of students’ acceptance and misconceptions of evolution is an area of great interest for science education stakeholders (Wang et al, 2022 ). Despite this interest, very little is known in this respect in countries such as Chile (Larrain et al, 2021 ; Marín et al, 2021 ), Colombia (Archila & Molina, 2020 ; Marín et al, 2021 ), Brazil (Demetrio et al, 2021 ), and Greece (Mantelas & Mavrikaki, 2020 ). Thus, in this article, we report the misconceptions about evolution among STEM/non-STEM majors of different ages, genders, and semester of administration of the 21-item questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on exploring the views of students about evolution in countries where there is little information documented in this respect, such as Chile (Larrain et al, 2021 ; Marín et al, 2021 ), Colombia (Archila & Molina, 2020 ; Marín et al, 2021 ), Brazil (Demetrio et al, 2021 ), and Greece (Mantelas & Mavrikaki, 2020 ). The present study seeks to contribute to this exploration, particularly in Colombia.…”
Section: Introductionmentioning
confidence: 99%